Evaluating the causal effects of life-course adiposity on jaw anomalies - Xin Chen; Zheng Cheng; Qianyi Wang; Yubin Jiang; Qing Cheng; Qianglin Jiang (Progress in Orthodontics)
Abstract Background Observational studies indicate that obesity correlates with jaw development and remodeling; however, causality remains unclear. This study aimed to examine the potential causal relationship between life-course adiposity and jaw anomalies. Methods Utilizing summary statistics from genome-wide association studies predominantly of European ancestry, we conducted univariable and multivariable Mendelian randomization (MR) to estimate overall and independent effects of six obesity traits (birth weight, childhood body size, childhood body mass index [BMI], adult BMI, adult body fat percentage, and adult waist circumference) on seven jaw anomalies, including bimaxillary hypoplasia, prognathism, retrognathism, and jaw asymmetry. Comprehensive sensitivity analyses verified robustness, assessed heterogeneity, and examined pleiotropy. Results In univariate analyses, genetically predicted thinner childhood body size (inverse variance weighted [IVW] OR: 0.41, 95% CI: 0.27–0.62, p < 0.001), adult BMI (IVW OR: 0.65, 95% CI: 0.53–0.80, p < 0.001), and waist circumference (IVW OR: 0.60, 95% CI: 0.45–0.82, p = 0.001) were significantly associated with the risk of mandibular retrognathia following Bonferroni correction. Multivariable MR analysis revealed a direct causal effect of childhood body size on mandibular retrognathia, independent of birth weight, adult adiposity, growth hormones, and lifestyle factors. No evidence was found for causal associations between life-course adiposity and other jaw anomalies. Sensitivity analyses produced broadly consistent findings. Conclusions This MR study provides new evidence on the direct causal effects of thin childhood body size on the risk of mandibular retrognathia, emphasizing the critical role of early childhood nutrition and weight management in craniofacial development.